2016
DOI: 10.2147/ott.s95457
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of failure and survival in patients with nasopharyngeal carcinoma treated with intensity-modulated radiation therapy in Saudi Arabia

Abstract: BackgroundWe aimed to investigate the patterns of failure (locoregional and distant metastasis), associated factors, and treatment outcomes in nasopharyngeal carcinoma patients treated with intensity-modulated radiation therapy (IMRT) combined with chemotherapy.Patients and methodsFrom April 2006 to December 2011, 68 nasopharyngeal carcinoma patients were treated with IMRT and chemotherapy at our hospital. Median radiation doses delivered to gross tumor volume and positive neck nodes were 66–70 Gy, 63 Gy to cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…For the whole cohort, our study revealed survival outcomes comparable to the published literature from the endemic region and favorable to previous studies from our region that used non-IMRT techniques or small series IMRT technique. 8 9 11 This study did not show a survival advantage for induction over the no-induction group; the 3-year OS and DFS were 92.7% and 79.67% in the induction group and 92.9% and 93.28% in the no-induction group, respectively. As shown in Table 1 , the majority of patients in the induction group had advanced T and N categories compared with the no-induction group.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…For the whole cohort, our study revealed survival outcomes comparable to the published literature from the endemic region and favorable to previous studies from our region that used non-IMRT techniques or small series IMRT technique. 8 9 11 This study did not show a survival advantage for induction over the no-induction group; the 3-year OS and DFS were 92.7% and 79.67% in the induction group and 92.9% and 93.28% in the no-induction group, respectively. As shown in Table 1 , the majority of patients in the induction group had advanced T and N categories compared with the no-induction group.…”
Section: Discussionmentioning
confidence: 75%
“…There are limited data on survival outcomes, patterns of failure, acute and late toxicity from the Middle East region. 8 9 Herein, we retrospectively evaluated the clinical outcomes, patterns of failure, acute and late toxicities of NPC patients treated with CCRT with or without IC or AC at our institution.…”
Section: Introductionmentioning
confidence: 99%
“…The problem is more challenging in patients with advanced stages. Maklad et al 29 reported an overall failure of treatment in 21 out of 68 Saudi patients with nasopharyngeal cancer. Out of 21, seven were locoregional, 3 were regional with DM, and 11 had DM.…”
Section: Discussionmentioning
confidence: 99%